THE INFLUENCE OF EMPLOYER BRANDING ON ATTRACTING AND RETAINING HIGH-POTENTIAL EMPLOYEES - Firman Arifianto; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the influence of employer branding on attracting and retaining high-potential employees (HiPos). In the competitive knowledge economy, organizations struggle to secure and keep top talent, with traditional tactics often failing for the high-expectation HiPo cohort. Through qualitative analysis, this research identifies the key employer branding dimensions HiPos value most, revealing a distinct preference for Development and Interest value over generic benefits. The findings demonstrate employer branding's dual role: it functions as an external "Magnet" for attraction and an internal "Glue" for retention, with the fulfillment of the psychological contract being the critical link. The study concludes that to effectively manage HiPo talent, organizations must tailor their Employer Value Proposition to these specific drivers and ensure consistent delivery on their brand promises through aligned HR systems and managerial action.